DEVELOPMENT OF MSME HUMAN RESOURCE MANAGEMENT BASED ON KNOWLEDGE MANAGEMENT IN INDONESIA - Supardi Supardi (Jurnal Ekonomi, 2022)
More than 90 percent of the economic sector in Indonesia is comprised of MSMEs, making them the economic engine of the country. To succeed in an increasingly competitive business environment, MSME operators must be able to cultivate their human capital. Increasing employees' expertise is one aspect of HR development. Therefore, in a competitive context, Knowledge Management must be implemented by SMBs. This study intends to assess the growth of knowledge management-based small and medium-sized enterprises (SME) in Indonesia from an HRM viewpoint. This research employs a qualitative descriptive methodology. The results of the study indicate that as competition increases, MSMEs must be able to overcome their deficiencies, innovate swiftly, and develop goods efficiently through knowledge manager-based HR management. Knowledge management is required to create MSME competitiveness since knowledge is the key to success in beating the competition. Knowledge management and HRM are crucial to enhancing the competitiveness of micro, small, and medium-sized enterprises (MSMEs) because they facilitate the transformation of HR knowledge into organizational knowledge, thereby creating MSME assets.